Local Hölder continuity of weak solutions to a diffusive shallow medium equation - Singer, Thomas; Vestberg, Matias (Nonlinear Analysis - Theory Methods & Applications, 2019)
We show the local Hölder continuity of bounded weak solutions to a doubly nonlinear parabolic equation used in models for diffusion of shallow media.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Doubly nonlinear parabolic equations; Local Hölder continuity